Harmonization of Tradition and Islam: Mediating Culture and Religious Beliefs in Maccera Tasi Ritual in Luwu, South Sulawesi - Azka, Ibnu; Fathur Baldan Haramain; Mohammad Cholil Alwi (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2024)
This study explores the Maccera Tasi tradition in Bonepute Village, Luwu Regency, South Sulawesi, examining its intersection with Islam and local culture. Recently, the Indonesian Ulema Council (MUI) of South Sulawesi deemed this long-standing tradition as shirk, or polytheistic, asserting that it contradicts Islamic law. This declaration was made by the MUI’s fatwa commission following public reports about rituals involving offerings of livestock heads, such as cows, buffalo, or goats, or other food into the ocean. In response to these reports, the Regional MUI team conducted a field research whose findings were reported to the South Sulawesi MUI. This report served as the basis for the aforementioned announcement. While some perceive the Maccera Tasi practice as an expression of gratitude for the harvest, others label it as shirk (polytheism). The present study employed field research, utilizing qualitative descriptive analysis. Data were collected through observation, interviews, and documentation. The research participants included religious leaders, traditional leaders, community leaders and local government representatives from Bonepute. The findings of this research suggest that religion and local traditions can coexist, fostering social cohesion without infringing upon Islamic law. This harmonious coexistence encourages the Bonepute community, particularly fishermen, to express gratitude for the blessings bestowed by Allah SWT. This gratitude is manifested through prayer, the release of seeds, and marine fish food, which are interpreted as forms of environmental stewardship. Therefore, this study contends that the perception of the Maccera Tasi practice as polytheistic is inaccurate. Instead, this practice represents an Islamic expression of preserving local culture through a process of religious and cultural assimilation.